2010
DOI: 10.1016/j.jcrs.2010.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Apodized diffractive intraocular lens implantation after laser in situ keratomileusis with or without subsequent excimer laser enhancement

Abstract: Apodized diffractive multifocal IOL implantation and excimer laser enhancement in eyes with previous myopic LASIK provided good results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 28 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…A few studies have reported the distance and near VA after implantation of the ReSTOR SN60D3 and SN6AD3 (Alcon Laboratories Inc.) and AT LISA 809M MIOL (Carl Zeiss Meditec AG) in patients who underwent previous myopic [14, 16, 17] and hyperopic LASIK procedures [15, 18]. In those studies, the intermediate VA was not measured [1517] or was presented in the form of a defocus curve without an exact value [14, 18]. The CS, binocular vision, visual symptoms, and satisfaction data were also unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have reported the distance and near VA after implantation of the ReSTOR SN60D3 and SN6AD3 (Alcon Laboratories Inc.) and AT LISA 809M MIOL (Carl Zeiss Meditec AG) in patients who underwent previous myopic [14, 16, 17] and hyperopic LASIK procedures [15, 18]. In those studies, the intermediate VA was not measured [1517] or was presented in the form of a defocus curve without an exact value [14, 18]. The CS, binocular vision, visual symptoms, and satisfaction data were also unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…in 2010 published the results following MFIOL implantation (ReSTOR SA60D3 and ReSTOR SN60D3) in 49 eyes that had the previous LASIK for myopia. [ 26 ] No single formula was used uniformly for all patients. At 1 month, 32 eyes (65%) and 41 eyes (84%) had a residual spherical equivalent within ±0.50D and ±1.0 D of emmetropia, respectively.…”
Section: Preoperative Evaluation and Planningmentioning
confidence: 99%
“…It has been reported that the number of eyes requiring laser surgery enhancement may be has high as 42.9%, but all enhancements achieved a safe and satisfactory result. 13 If the residual refractive error solely remains as astigmatism, some surgeons prefer to safely correct the astigmatism with limbal relaxing incisions instead of pursuing laser surgery enhancements. 14 ' Biometry Biometry includes standard keratometry measurements and an ultrasound scan.…”
Section: History Of Corrective Refractive Surgery or Residual Refractmentioning
confidence: 99%